Current status of diabetes treatment in Miyazaki Prefecture, Japan: Results of a questionnaire survey conducted in 2016 and 2020. Issue 6 (9th March 2022) - Uehira, Yudai; Ueno, Hiroaki; Ebihara, Emi; Uchida, Taisuke; Nabekura, Hiroki; Sakoda, Hideyuki; Yonekawa, Tadato; Yamaguchi, Hideki; Nakazato, Masamitsu
ABSTRACT: Aims/Introduction: The Japanese diabetes treatment guidelines do not specify the first choice of hypoglycemic agents, unlike those of Western countries. Furthermore, the current situation in diabetes treatment is that the choice of hypoglycemic agents is determined by each physician. Therefore, we aimed to determine the current situation in Miyazaki Prefecture, Japan, in this context. For this, we carried out a questionnaire survey among physicians twice regarding the target value of glycated hemoglobin and the choice of hypoglycemic agents in various cases. Materials and Methods: We administered an unsigned questionnaire to physicians in Miyazaki Prefecture, Japan, in July 2016 and March 2020. We divided responses into those of diabetologists and those of non‐diabetologists, and analyzed each response. We then compared the results between both years. Results: In total, 18 diabetologists and 142 non‐diabetologists responded in 2016, and 21 diabetologists and 134 non‐diabetologists responded in 2020. Many diabetologists chose biguanide as the first‐line drug for obese type 2 diabetes patients. In addition, the rate of choice of sodium–glucose cotransporter 2 inhibitor (SGLT2i) among physicians almost increased in 2020. Some non‐diabetologists, and even a few diabetologists, inappropriately chose SGLT2i and biguanide for patients with severe renal dysfunction. Conclusions: Because SGLT2i became available in 2016 and a few years have passed, both diabetologists and non‐diabetologists seemed to refrain from prescribing SGLT2i. However, with the emergence of various lines of firm evidence regarding the use of SGLT2i, physicians started to prescribe it. However, some diabetologists and non‐diabetologists chose hypoglycemic agents inadequately; therefore, there is a need for novel and precise information. Abstract : We carried out a questionnaire survey among physicians twice regarding the target value of glycated hemoglobin and the choice of hypoglycemic agents in various cases, and divided the responses into those of diabetologists and those of non‐diabetologists. We analyzed each response and compared the results between both years.